Synthesis, Antibacterial Potential and In Silico Molecular Docking Analysis of Triazene Compounds via Diazo Coupling Reactions of an Amine - Ainaa Nadiah, Abd Halim; AINA SYAKIRAH, MOHAMMAD HUSSIN; Zainab, Ngaini; Nor Hisam, Zamakshshari; Izzhan Zafri, Haron (Elsevier B.V., 2023)
In the drug discovery and development process, structure-based drug design is essential to ensuring the effectiveness and efficiency of the drugs towards the target receptor. The preparation of a compound with the structural capability to form strong interactions with the receptor is predicted to have stronger therapeutic activity. Herein, a series of N-coupling aromatic triazene compounds 1–13, bearing electron-withdrawing and electron-donating groups at ortho, meta, and para positions were successfully synthesized via diazo coupling reactions of substituted anilines with 4′-aminoacetanilide with reasonable yields of 15–60 %. The antibacterial potential of the compounds was screened against Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) employing the turbidimetric kinetic method, which showed promising minimum inhibitory concentration (MIC) values of 62–185 ppm and 63–158 ppm, respectively. Among all, compounds 1 (H) and 4 (p-F) exhibited excellent bacterial inhibition against both screened bacteria, 83 ppm and 68 ppm (S. aureus) and 63 ppm and 84 ppm (E. coli), respectively outperforming the standard ampicillin 85 ppm (S. aureus) and 86 ppm (E. coli). The in silico molecular docking analysis targeted Dehydrosqualene synthase (CrtM) and DNA gyrase enzymes, which demonstrated binding scores of −8.1 kcal/mol and −8.9 kcal/mol for compound 1 and −8.2 kcal/mol and −8.5 kcal/mol for compound 4, respectively.